2023
DOI: 10.30595/pssh.v12i.835
|View full text |Cite
|
Sign up to set email alerts
|

Development of Ecological Citizenship-Based Character Education Model to Improve Environmental Naturalistic Intelligence of Elementary School Students

Dewi Rakhmawati,
Haryanto Haryanto,
Murdiono Murdiono
et al.

Abstract: The lack of naturalistic intelligence in students can have an impact on students' understanding of the environment and nature. Naturalistic intelligence can help students understand the importance of protecting the environment and being responsible for preserving the environment. Therefore, the purpose of this study is to develop an Ecological Citizenship-Based Character Education Model to Improve Environmental Naturalistic Intelligence of Elementary School Students. A research and development (RnD) research d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Research has demonstrated that the provision of spare parts media, which can be utilized to augment the naturalist intelligence of Preschool children, has a significant impact. Furthermore, research has demonstrated the efficacy of the ecological citizenshipbased character education paradigm in enhancing the environmental naturalist intelligence of students (Rakhmawati & Kawuryan, 2023). Therefore, naturalist intelligence in education is essential to foster a deeper understanding of the environment and promote environmental literacy.…”
Section: Naturalistic Intelligencementioning
confidence: 99%
“…Research has demonstrated that the provision of spare parts media, which can be utilized to augment the naturalist intelligence of Preschool children, has a significant impact. Furthermore, research has demonstrated the efficacy of the ecological citizenshipbased character education paradigm in enhancing the environmental naturalist intelligence of students (Rakhmawati & Kawuryan, 2023). Therefore, naturalist intelligence in education is essential to foster a deeper understanding of the environment and promote environmental literacy.…”
Section: Naturalistic Intelligencementioning
confidence: 99%